2014
DOI: 10.1007/s10827-014-0520-x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling fast forms of visual neural plasticity using a modified second-order motion energy model

Abstract: The Adelson-Bergen motion energy sensor is well established as the leading model of low-level visual motion sensing in human vision. However, the standard model cannot predict adaptation effects in motion perception. A previous paper presented an extension to the model which uses a first-order RC gain-control circuit (leaky integrator) to implement adaptation effects which can span many seconds, and showed that the extended model's output is consistent with psychophysical data on the classic motion after-effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…They further reported that the first-order leaky integrator was sufficient to implement adaptation effects of long durations which can span many seconds. However, a second-order leaky integrator, which causes the sensor to require a finite amount of time to react to a sudden change in stimulation, was critical for the rapid form of MAE (Pavan, Contillo, & Mather, 2014). These findings clearly demonstrate that the neural mechanisms operating over different timescales can be supported and recruited in the same neural substrate.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…They further reported that the first-order leaky integrator was sufficient to implement adaptation effects of long durations which can span many seconds. However, a second-order leaky integrator, which causes the sensor to require a finite amount of time to react to a sudden change in stimulation, was critical for the rapid form of MAE (Pavan, Contillo, & Mather, 2014). These findings clearly demonstrate that the neural mechanisms operating over different timescales can be supported and recruited in the same neural substrate.…”
Section: Discussionmentioning
confidence: 75%
“…These findings clearly demonstrate that the neural mechanisms operating over different timescales can be supported and recruited in the same neural substrate. According to Pavan et al (2014) and previous research (e.g., Wark, Fairhall, & Rieke, 2009), the temporal dynamics of adaptation may reflect a balance between adapting rapidly to avoid short-term saturation and adapting slowly (over longer timescales) to avoid instability in the absence of changes in image statistics. This is because changes in natural scenes occur over multiple Fig.…”
Section: Discussionmentioning
confidence: 92%